2021
DOI: 10.1021/acsami.1c02977
|View full text |Cite
|
Sign up to set email alerts
|

A First Molecular Dynamics Study for Modeling the Microstructure and Mechanical Behavior of Si Nanopillars during Lithiation

Abstract: This is the first study that employs large-scale atomistic simulations to examine the stress generation and deformation mechanisms of various Si nanopillars (SiNPs) during Li-ion insertion. First, a new robust and effective minimization approach is proposed to relax a lithiated amorphous SiNP (a-SiNP), which outperforms the known methods. Using this new method, our simulations are able to successfully capture the experimental morphological changes and volume expansions that SiNPs, hollow a-SiNPs, and solid cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In the study on lithium ion battery electrodes, researchers observed that the intercalation of Li + ions generates stresses and strains in electrodes that generally cause performance degradation, whereas this composition–stress coupling provides a new idea for mechanical energy harvesting. Kim et al recently demonstrated an approach to convert mechanical energy through an electrochemical route .…”
Section: Introductionmentioning
confidence: 99%
“…In the study on lithium ion battery electrodes, researchers observed that the intercalation of Li + ions generates stresses and strains in electrodes that generally cause performance degradation, whereas this composition–stress coupling provides a new idea for mechanical energy harvesting. Kim et al recently demonstrated an approach to convert mechanical energy through an electrochemical route .…”
Section: Introductionmentioning
confidence: 99%
“…First, different geometrical constraints generate the distinct stress fields. For instance, biaxial stress occurs in the lithiated Si thin films, owing to the substrate constraints. Such biaxial stress in a -Li x Si is lower than the intrinsic yield stresses of a -Li x Si, owing to the reaction-assisted plastic flow in a -Li x Si. , As in Si particles with only one-phases states, computational studies demonstrate that lithiation leads to the tensile radial stress, while the compressive-to-tensile hoop stress transitions from the outer to inner parts of Si particles. , The compressive surface stress reduces the Li diffusivity and blocks the lithiation process. , Second, the competition between reaction kinetics and Li diffusion rates determines the lithiation process and subsequent stress states in Si anodes. If the reaction kinetics is much slower than the Li diffusion rate, the lithiation of Si particles occurs in a two-phase way, , in which the inner pure Si phase is separated from the outer fully lithiated phase by a sharp phase interface. In such case, both radial and hoop stresses are compressive in the inner Si phases, compared with the tensile ones in the outer lithiated phase. , The tensile surface stress may fracture the outer shell; meanwhile, the compressive one at the phase interface can highly increase the energy barrier for lithiation kinetics. Finally, battery operating conditions may mechanically degrade Si anodes.…”
Section: Introductionmentioning
confidence: 99%